2011
DOI: 10.1016/j.transproceed.2011.08.074
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profile Changes During the First Year After Kidney Transplantation: Risk Factors and Influence of the Immunosuppressive Drug Regimen

Abstract: Dyslipidemia is frequent at 1 year after transplantation. The lack of agreement among changes observed in lipid fractions and ratios suggests that more studies are necessary to guide therapy besides targeting LDL-C concentrations as recommended by current guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 25 publications
4
49
2
1
Order By: Relevance
“…Several clinical studies have shown that immunosuppressants increase serum levels of cholesterol, TG and LDL-C, usually in a dose-dependent manner. 57,58 In the present study, KTR and CRF patients had increased TG levels compared with those of the control group. Lp (a) and apo B were also significantly higher in CRF cases compared to controls.…”
Section: Discussionsupporting
confidence: 45%
“…Several clinical studies have shown that immunosuppressants increase serum levels of cholesterol, TG and LDL-C, usually in a dose-dependent manner. 57,58 In the present study, KTR and CRF patients had increased TG levels compared with those of the control group. Lp (a) and apo B were also significantly higher in CRF cases compared to controls.…”
Section: Discussionsupporting
confidence: 45%
“…In most clinical studies, sirolimus treatment is associated with a significant increase in LDL cholesterol (40,43,47). In the study performed by Spinelli et al (43), sirolimus treatment was an independent factor associated with plasma LDL cholesterol levels above 121 mg/dl.…”
Section: Effects Of Mtor Inhibitors On Lipids "mentioning
confidence: 97%
“…In most clinical studies, sirolimus treatment is associated with a significant increase in LDL cholesterol (40,43,47). In the study performed by Spinelli et al (43), sirolimus treatment was an independent factor associated with plasma LDL cholesterol levels above 121 mg/dl. It has also been reported that treatment with sirolimus is associated with a dramatic increase in plasma triglycerides ranging from 65 to 100% (41,42,43,44,45,47).…”
Section: Effects Of Mtor Inhibitors On Lipids "mentioning
confidence: 97%
See 2 more Smart Citations